Temperature evolution and runoff contribution of three rock glaciers in Switzerland under future climate forcing - Pruessner, Luisa; id_orcid:0 000-0001-8125-2426; Huss, Matthias; id_orcid:0 000-0002-2377-6923; Farinotti, Daniel; id_orcid:0 000-0003-3417-4570 (Wiley, 2022)
With ongoing climate change water availability in the source regions of alpine streams are at stake. In particular, dry mountain regions which currently rely on glacial meltwater will need to adapt. Since rock glaciers are more resilient to climate change and occur in nearly all high-mountain catchments around the globe with some form of glacierization, it is of interest to investigate their contribution to runoff under different climate scenarios. Three well-monitored rock glacier sites in the Swiss Alps (Murtel, Ritigraben, and Schafberg) have been investigated under the climate change scenarios corresponding to low, medium and high greenhouse gas emissions to determine how their runoff contribution is affected. By the end of the 21st century, runoff from permafrost melting could account for 5-12% (12.0% for Murtel, 7.0% for Ritigraben, and 5.0% for Schafberg) of monthly catchment runoff at maximum in an average year, and up to 50% in extreme years. For the low-emission scenario, little change in the runoff contribution from rock glaciers is found, while the medium-emission scenario shows increased variability and a shift in the seasonal runoff peak to earlier in the year. The high-emission scenario indicates a further increase in the variability of the permafrost runoff contribution and also the development of a secondary seasonal peak in autumn, most prominently in the late century. ISSN:1045-6740 ISSN:1099-1530